Prevalence of Asymptomatic Uterine Leiomyoma in Western Turkey and Factors Affecting Myoma Presence - Fatma Nurgul Tasgoz; Nergis Kender Erturk (Gynecology Obstetrics & Reproductive Medicine)
Objective: To reveal the prevalence of asymptomatic uterine leiomyomas among gynecologic patients and to evaluate risk factors associated with the presence of leiomyomas.